BIOREMEDIATION TO REDUCE PESTICIDE POLLUTION ON AGRICULTURAL LAND - Setyono Prabang; Hawali Abdul Matin Hashfi; Sembiring Tarzan; Kinanthi Putri Febriana; Agung P Ekaputra (Journal of Agronomy Research, 2023)
Environmental pollution until this moment still become crucial environmental problem. Environmental pollution can occur anywhere, one of them is in agriculture sectoral. Environmental pollution in the agriculture area caused by usage of chemical pesticide for managing agriculture. Using chemical pesticide can leave residue that raises pollution. Bioremediation become one of the solutions for the problem. Besides it is environmental friendly, bioremediation is also easy to apply and cheap. This study aim to examine the potency of Bacillus altitudinis , Bacillus subtilis, Pseudomonas b68, and Pseudomonas b70 as biological agent for bioremediation of pesticide residues in soil Biological agent was incubated in liquid medium polluted pesticide type fungicide for 15 days on some variation concentration pesticides (100, 200, 300) mg/L. Concentration of pesticides and values Optical density (OD) is measured every 3 days with spectrophotometer UV -Vis on long 280 nm and 578 nm waves. The Results showed that the bioagents lower pesticides concentration. and can growing under polluted pesticides conditions The effectiveness and decline in pesticide residue by Bacillus altitudinis ranged from 49.91-59.33%; Bacillus subtilis (50.06-60.51%); Pseudomonas b68 (81.32-86.13 %); Pseudomonas b70 (50.02- 62.1 %). The bioagents produced decreases in the concentration of pesticides, increase in OD value, and decrease in pH indicate. The results affirmed that Bacillus altitudinis, Bacillus subtilis, Pseudomonas b68, and Pseudomonas b70 are effective as bioagents in the remediation pesticides polluted soils
Keywords: Bioremediation